2021
DOI: 10.2147/opth.s321594
|View full text |Cite
|
Sign up to set email alerts
|

Intraretinal Cysts in Macular Hole: A Structure-Function Correlation Based on En Face Imaging

Abstract: Purpose: To characterize retinal micromorphic changes on en face optical coherence tomography (OCT) and to determine their role in pathogenesis and visual outcomes in macular hole (MH) surgery. Patients and Methods: This is a retrospective, interventional, consecutive case series of 28 eyes undergoing successful MH surgery. Pre-and post-operative en face OCT were manually segmented, and the correlation between parameters such as MH basal diameter and minimal inlet area, area of cyst in inner plexiform layer (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Ozturk et al conducted an analysis of cyst and MH dimensions, revealing a moderate negative correlation with postoperative BCVA [36]. Similarly, Nair et al observed that the sizes of parafoveal intraretinal pseudocysts were linked to a lower closure rate and diminished postoperative BCVA [37]. Ruiz-Moreno et al showed that individuals with cystic retinal changes had lower mean preoperative and postoperative VAs compared to those without such changes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Ozturk et al conducted an analysis of cyst and MH dimensions, revealing a moderate negative correlation with postoperative BCVA [36]. Similarly, Nair et al observed that the sizes of parafoveal intraretinal pseudocysts were linked to a lower closure rate and diminished postoperative BCVA [37]. Ruiz-Moreno et al showed that individuals with cystic retinal changes had lower mean preoperative and postoperative VAs compared to those without such changes [38].…”
Section: Discussionmentioning
confidence: 99%